THE PHENOMENON OF THERMODYNAMIC ACTION DURING PLASTIC DEFORMATION OF METALS AND THEIR ALLOYS (Modern Problems of Metallurgy, 2024)
The most important problem of modern technology for mechanical processing of structural materials is to increase the efficiency of shaping operations. Its full value solution requires the establishment of a functional relationship between the parameters of the force influence on the workpiece and the characteristics of the natural adaptive behavior of the processed material. In this regard, using metals and their alloys as an example, the mechanism and general laws of thermodynamic excitation of solid crystalline bodies during plastic deformation are considered. The relationship between the change in the thermodynamic potentials of the substance of the deformed volume and its behavior during the process of shape forming, as well as in the postoperative period, is described. It is shown based on the synergetic method of analyzing highly nonequilibrium systems that from a technological point of view the most favorable adaptive functional response arises in the case when the deforming influence is exerted taking into account the natural ability of the workpiece substance to relaxation. The got results create the basis for improving the operations of mechanical processing of metals and their alloys by taking into consideration the properties and features of the natural deformation behavior of each concrete material under concrete conditions. They are applicable not only for metal forming operations, but also in cutting technology.
Keywords: metals and their alloys; pressure processing; mechanical action; thermodynamic excitation; thermodynamic potentials; thermodynamic action; deformation behavior.